2016
DOI: 10.1111/1911-3846.12239
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Pricing: Strategies, Practices, and Tax Minimization

Abstract: Using a survey of tax executives from multinational corporations, we document that some firms set their transfer pricing strategy to minimize tax payments, but more firms focus on tax compliance. We estimate that a firm focusing on minimizing taxes has a GAAP effective tax rate that is 6.6 percentage points lower and generates about $43 million more in tax savings, on average, than a firm focusing on tax compliance. Available COMPUSTAT data on sample firms confirm our surveybased inferences. We also find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(61 citation statements)
references
References 84 publications
2
48
1
10
Order By: Relevance
“…So, we also consider Int'l to increase the expected future cash flows from transfer pricing activities. Klassen et al () found evidence that tax directors with greater transfer pricing experience are correlated with a lower effective tax rate. We operationalize the target's previous experience as part of a multinational group with Int'l , equal to one if the target's nation and the nation of the ultimate parent of the target prior to the acquisition are not the same, and equal to zero otherwise…”
Section: Tests Of the Hypothesesmentioning
confidence: 99%
“…So, we also consider Int'l to increase the expected future cash flows from transfer pricing activities. Klassen et al () found evidence that tax directors with greater transfer pricing experience are correlated with a lower effective tax rate. We operationalize the target's previous experience as part of a multinational group with Int'l , equal to one if the target's nation and the nation of the ultimate parent of the target prior to the acquisition are not the same, and equal to zero otherwise…”
Section: Tests Of the Hypothesesmentioning
confidence: 99%
“…(e.g. survey evidence by Klassen et al, 2017, Hoopes et al, 2015, evidence from archival data by Hopland et al, 2017, de Simone, 2016, Kim et al, 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Market price-based transfer prices for internally traded products are often used as a value measure for the decentralised management of internal production processes (Wolff, 2007). Using a survey of tax executives from multinational corporations, Klassen et al (2017) documents that some firms set their transfer pricing strategy to minimize tax payments, but more firms focus on tax compliance.…”
Section: Literature Reviewmentioning
confidence: 99%